Clinical and Surgical Analysis of Periorbital Dermoid Cysts: A Retrospective Evaluation of 16 Cases - Derya Doğanay (Journal of Bursa Faculty of Medicine, 2026)
Objectives: To evaluate the clinical, radiological, and surgical characteristics of patients treated surgically for periorbital dermoid cysts and to present our treatment outcomes in light of the current literature.Methods: Data from 16 patients diagnosed with periorbital dermoid cysts and treated with surgical excision at our clinic between January 2020 and May 2026 were retrospectively reviewed. Demographic characteristics, cyst localization, radiological findings, surgical techniques, intraoperative complications, and follow-up periods were analyzed.Results: Of the 16 patients included, 10 (62.5%) were female and 6 (37.5%) were male, with a mean age of 7.68 ± 10.75 years (range 2–43). The lesions were located on the right eye in 10 cases (62.5%) and the left eye in 6 cases (37.5%). Regarding anatomical localization, 10 cases (62.5%) were lateral, 3 (18.75%) were medial, and 3 (18.75%) were located in the lid sulcus. Surgical excision was performed under general anesthesia for all patients. Intraoperative cyst rupture occurred in two patients (12.5%); one adult patient presented with liquefied cyst content and developed postoperative inflammation. No recurrence was observed during the mean follow-up period of 23.62 ± 15.73 months.Conclusion: Periorbital dermoid cysts are the most common orbital masses in childhood. The primary treatment approach is total surgical excision while maintaining the integrity of the cyst wall. Careful selection of the incision site for cosmetic results and meticulous dissection to prevent complications ensure successful outcomes and low recurrence rates.